Peroxisome Proliferator-Activated Receptors Protect against Apoptosis via 14-3-3 - Kenneth K. Wu (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) were reported to prevent cells from stress-induced apoptosis and protect tissues against ischemia-reperfusion injury. The underlying transcriptional mechanism is unclear. Recent reports indicate that the antiapoptotic actions of ligand-activated PPARδ and PPARγ are mediated through enhanced binding of PPAR to the promoter of 14-3-3ε and upregulation of 14-3-3ε expression. We propose that ligand-activated PPARα exerts its anti-apoptotic actions via the identical pathway. The PPAR to 14-3-3 transcriptional axis plays an important role in protection of cell and tissue integrity and is a target for drug discovery.